Importancia del conejo zacatuche (Romerolagus diazi) en la dieta del coyote (Canis lastrans) y del lince (Lynx rufus) - Uriostegui Velarde, Juan Manuel; Vera García, Zuri Samuel; Ávila Torresagatón, Luis Gerardo; Rizo Aguilar, Areli; Hidalgo Mihart, Mircea Gabriel; Guerrero, José Antonio (THERYA, 2015)
Introduction: Predation may have important effects on prey populations, especially when the prey species is considered endangered such as the volcano rabbit (Romerolagus diazi). Understanding the importance of the volcano rabbit in the coyote and bobcat diet is important to recognize the possible impact that thesepredators can have on the populations of this endangered rabbit. Methods: We studied the food habits of the coyote and during three climate seasons in the Chichinautzin Biological Corridor through scat analysis. We obtained the frequency of occurrence and consumed biomass of each identified prey item. Additionally we estimated the relative abundance of some of the potential prey species for these two predators and analyzed the relationship between prey abundance and the use of the prey found on the diet of these two predators. Results: The most common prey species and with the greatest biomass contribution on the diet of coyotes and bobcats were the rabbits of the genus Sylvilagus sp., followed by the volcano rabbit. We did not find differences in the frequency of occurrence of prey or in the consumed biomass between the studied seasons, indicating that the diet of both predators remains constant throughout the year. Prey selection analysis showed that both predators selected Sylvilagus rabbits, while volcano rabbits are consumed less than their availability in the environment. Discussion and conclusions: Reduced consumption of the volcano rabbit according with their availability on the environment by coyotes and bobcats could be the result of the selection of larger prey and the nocturnal behavior patterns of both predators. Even though we did not find that both predators are selecting volcano rabbits on their diets, our results showed that coyotes and bobcats are important predators for R. diazi. It is necessary to determine the potential number of volcano rabbits consumed by both predators in order to understand the impact of these predators on this endangered species.